Pemanfaatan Limbah Minyak Goreng Dari Hasil Kuliner Pecel Lele Menjadi Biodiesel - Indah Sukria; Andi Arif Setiawan; Rahmawati Rahmawati; Muhammad Hapiz Hermansyah (Universitas PGRI Palembang, 2022)
The activity of making biodiesel from waste oil from pecel catfish is useful for reducing environmental pollution due to waste disposal, and reducing damage to the human body due to repeated consumption of oil. This study aims to analyze the quality of biodiesel from waste oil using a NaOH catalyst and with different variations of methanol content of 75%, 80%, 85% and 95%. The method used is an experiment in the laboratory. The addition of methanol with different levels of variation was measured for viscosity, density, moisture content and flash point with three repetitions. The results of these measurements indicate that the use of methanol with a level of 95% that meets the SNI standard with the results of an average viscosity of 5.1 cSt, an average density of 0.87 g/cm3, water content shows an average of 0.37% and average flash point 3500C.